Determining Promotion Priority Using TOPSIS on Trilogi University - Qassandra Chaidir; Rudi Setiawan (Journal of Information System and Informatics, 2022)
Promotion is one way to achieve sales targets, private universities are also inseparable from the need for promotions to increase the number of student admissions so it is necessary to carry out various strategies to achieve the targets that have been set so that the promotions carried out by Trilogy University are right on target, a target analysis is needed. In this study, the TOPSIS method was used to rank schools that would be the target of promotion in the hope that promotional activities would be right on target and could increase the income of the number of new students. The results showed that the TOPSIS method was able to rank the target schools to be visited, from the ranking results showed that the number of applicants, the distance from school to university and the status of the school in collaboration with the education office had no significant effect on the ranking results.